Recent Advances in Ruthenium-Catalyzed Hydrogenation Reactions of Renewable Biomass-Derived Levulinic Acid in Aqueous Media - Seretis, Aristeidis; Diamantopoulou, Perikleia; Thanou, Ioanna; Tzevelekidis, Panagiotis; Fakas, Christos; Lilas, Panagiotis; Papadogianakis, Georgios (Frontiers in Chemistry, 2020)
Levulinic acid (LA) is classified as a key platform chemical for the development of future’s biorefineries owing to its broad spectrum of potential applications and because it is simply available from lignocellulosic biomass by inexpensive and high-yield production routes. Catalytic hydrogenation reactions of LA into the pivotal intermediate compound γ-valerolactone (GVL) and beyond GVL to yield valeric acid (VA), 1,4-pentanediol (1,4-PDO) and 2-methyltetrahydrofuran (2-MTHF) have gained considerable attention last decade. Among the various transition metals used as catalysts in LA hydrogenation reactions, ruthenium-based catalytic systems have been applied by far extensively due to the inherent ability of ruthenium under mild conditions to hydrogenate the keto functionality of LA selectively into an alcohol group to form 4-hydroxyvaleric acid intermediate which spontaneously after dehydration and cyclization yields GVL. This review focuses on recent advances in the field of aqueous-phase ruthenium-catalyzed hydrogenation reactions of LA towards GVL, VA, 1,4-PDO, 2-MTHF, 2-pentanol and 2-butanol employing heterogeneous catalysts on solid supports and heterogeneous water-dispersible catalytic nanoparticles or homogeneous water-soluble catalytic complexes with biphasic catalyst separation for the production, inter alia, of advanced biofuels such as valeric biofuels and other classes of liquid transportation biofuels, value-added fine chemicals, solvents, additives to gasoline and to food as well. The significance of the aqueous solvent to carry out catalytic hydrogenations of LA has been highlighted because the presence of water combines several advantages: (i) it is highly polar and thus an ideal medium to convert polar, hydrophilic substrates such as LA; (ii) water is involved as a byproduct; (iii) the presence of the aqueous solvent has a beneficial effect and enormously boosts hydrogenation rates. In sharp contrast, the use of various organic solvents gives rise to a dramatic drop in catalytic activities. The promotional effect of water was proved by numerous experimental investigations and several theoretical studies employing various types of catalytic systems; (iv) the large heat capacity of water renders it an excellent medium to perform large scale exothermic hydrogenations more safely and selectively; and (v) water is a non-toxic, safe, non-inflammable, abundantly available, ubiquitous, inexpensive and a green/sustainable solvent.